Pollen in the surface sediments of wetlands in the Becher Point area, southwestern Australia: a baseline for use in interpreting Holocene sequences - Semeniuk, Christopher; Milne, L.; Ladd, P.; Semeniuk, V. (Royal Society of Western Australia, 2006)
Pollen was collected from the surface sediments of 16 wetland basins situated on a beachridge plain in the Becher Point area, southwestern Australia. Sampling was undertaken to determine the ratio of wetland/upland plant species contributing to the surface pollen in each wetland, to determine the contributions of local and regional pollen, and to develop indicator pollen assemblages as a baseline to interpret fossil Holocene sequences. The main wetland plant assemblages colonising the wetlands include sedges - Baumea articulata (R. Br.) S. T. Blake;. TyphaL. spp.; mixed Baumea articulata and Typha spp.; Isolepis nodosa (Rottb.) R. Br.; Baumea juncea(R. Br.) Palla; Lepidosperma gladiatum Labill.; rushes - Juncus krausii Hochst.; grasses - Sporobolus virginicus (L.) Kunth.; shrubs - Melaleuca viminea Lindley; Melaleuca teretifolia Endl.; grass trees - Xanthorrhoea preissii Endl.; trees and shrubs - Melaleuca rhaphiophylla Schauer,Melaleuca cuticularis Labill. The pollen assemblages recovered from the surface sediments were separated into six categories as related to extant vegetation: that generated in situ from wetland basin vegetation; that derived from in situ wetland margin vegetation; that derived allochthonously from wetland vegetation; that from ridge vegetation (inhabiting the beachridges) and transportedto the wetland basin; that from distal vegetation in the region; and uncategorised pollen. Of the plants extant in modern wetland centres and their margins, the following key species were commonly detected as pollen grains in the surface sediment: Centella asiatica (L.) Urban, Baumeaarticulata, Baumea juncea, Isolepis nodosa, Lepidosperma gladiatum, Melaleuca cuticularis, Melaleuca viminea, Melaleuca rhaphiophylla, Melaleuca teretifolia, Sporobolus virginicus, Typhadomingensis Pers./T. orientalis C. Presl, and Xanthorrhoea preissii. In most wetlands, the majority of the surface pollen in the wetlands was derived from the local wetland and upland ridge vegetation (i.e., that inhabiting the beachridges) of the cuspate foreland. Generally, in situ wetland pollen constituted a moderate proportion of the total pollen. Wetland margin pollen was abundant in only half the wetlands. Pollen from ridges was sub-dominant to pollen from allochthonous wetland species in about half the wetlands, and dominant in the remainder. The contribution of distal pollen varied from low in most wetlands to relatively high numbers and significant in others.The potential dispersal mechanisms for pollen in this area are insects, avifauna, local processes of in situ generation, and easterly and westerly winds, and transport agents include wind, rain, sheet wash, and water transport. The differential effect of wind in transporting pollen was explored using local wetland species of Melaleuca as a signature, and the occurrence of upland species, such as Casuarinaceae spp., Olearia axillaris (DC.) F. Muell. ex Benth., and Eucalyptus marginata Donnex Smith pollen. The patterns show that delivery of pollen to the wetland basins is heterogeneous.